Ο Συγγραφέας μέσα στη διήγηση. Η περίπτωση του Βίου της Θεοφανούς - ΠΕΤΡΟΠΟΥΛΟΥ Αναστασία (Byzantina Symmeikta, 2021)
The Life of Theophano is a fine literary product (end of the ninth century). Although the author maintains his anonymity until the end of the Vita, his role in the narration is of great importance to the interpretation of the Life. He appears constantly behind the words and “winks” at his audience, while at the same time -in the last chapters of the hagiographical text- he and his family become active members of the narration and parallely the only recipients of saint’s miracles. This fact in combination with the glorified portrait of the emperor Leo VI, the presentation of Stylianos Zaoutzes as the savior of the emperor and the absence of any reference to patriarch Euthymios, the spiritual father of the imperial couple, constitute an interesting question. Undoubtedly the author’s special position in the narrative gives answers to the majority of the questions that the Life of Theophano raises.